AN ANALYSIS OF THE DECLINE OF THE MUGAL EMPIRE AND MUSLIM RULE IN INDIA - Kumar Singh, Dhupesh (International Journal of Multidisciplinary Research and Studies, 2020)
During Muammad Shah’s rule in the 18th century, the Mughal Empire started to fall (1719–48). The Marathas and then the British took over a large portion of its area. Bahdur Shah II (1837–57), the final Mughal emperor, was banished by the British because of his participation in the Indian Mutiny of 1857–1858. After Aurangzeb’s death in around 1707 CE, the Mughal Empire quickly went into collapse. The Great Mughal era is typically distinguished from the Later Mughal era by this year, which is also known as the dividing line year. You can read all about the later Mughals and the Mughal Empire’s decline in this article. This is a crucial subject for the section on UPSC test history. The rebirth of regional identities during the time between approximately 1707 CE and around 1761 CE (from Aurangzeb’s death to the time of the Third Battle of Panipat, where Ahmad Shah Abdali defeated the Maratha chiefs) revealed a sad state of affairs for the once-powerful Mughals. The Mughal court was the setting for feuds between the nobility. When Nadir Shah imprisoned the Mughal Emperor and pillaged Delhi in around 1739 CE, the empire’s frailties were made clear. Following the passing of Aurangzeb in around 1707 CE, a conflict over succession erupted between his three sons: Muazzam (the Kabul governor), Muhammad Kam Baksh (the governor of Deccan.